„Język jest domostwem bycia” (M. Heidegger). System rodziny jako przestrzeń dialogicznej relacji - Teusz , Grażyna (Studia Edukacyjne, 2020)
The article presents the family system as a space for dialogue. The text focuses both on the reality of the family, as a special community of persons in multiple interactions, and on linguistic structures and means of expression that contain potential, dialogical and communicative application. It is essential to reflect on the conditions which will ensure that the interpersonal relationships of the members of the family system are reflected in a genuine, authentic dialogue.